GUNS OF THE EASTER RISING - Smith-Christmas, Kenneth L (Acta Museologica Lithuanica, 2015)
After nearly 800 years of intermittent British domination, a group of Irish insurgents once again attempted to free their country from British rule during Easter Week, 1916. As many of them had expected, the Irish Volunteers were defeated after a week of heavy fighting in Dublin. Although the revolt was doomed to failure from the outset, a lack of arms and a disparity of arms and ammunition were factors in the defeat, although the Volunteers did have, and used to great effect, some modern weapons, such as the famous C96 Mauser pistol. However, the wide variety of weapons – antique single-shot Mauser rifles and Martini-Enfield carbines, obsolete Boer War rifles, and shotguns – in the hands of the Volunteers proved to be no match against the modern British Short Magazine Lee-Enfield rifle.